2015
DOI: 10.1186/s12950-015-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NLRP3 inflammasome in the transient release of IL-1β induced by monosodium urate crystals in human fibroblast-like synoviocytes

Abstract: BackgroundTo investigate whether monosodium urate (MSU) crystals induce interleukin (IL)-1β in human fibroblast-like synoviocytes (FLS), and whether the NLRP3 inflammasome is involved in the inflammatory mechanism.MethodsHuman FLS isolated from explants of synovial tissue were stimulated with MSU crystals (0.001 to 0.5 mg/ml) for different time course (6 hours to 48 hours). The expressions of IL-1β, IL-6, TNF-α and NLRP3 were evaluated with ELISA, Western blot and quantitative real-time PCR.ResultsExposure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
(53 reference statements)
3
33
1
Order By: Relevance
“…Second, signal 2 is transduced by various pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). Currently, several molecular mechanisms have been suggested for NLRP3 activation, including potassium efflux, lysosomal destabilization, and ROS generation [36, 37]. Our study revealed that procyanidins significantly decreased NLRP3 expression.…”
Section: Discussionsupporting
confidence: 49%
“…Second, signal 2 is transduced by various pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). Currently, several molecular mechanisms have been suggested for NLRP3 activation, including potassium efflux, lysosomal destabilization, and ROS generation [36, 37]. Our study revealed that procyanidins significantly decreased NLRP3 expression.…”
Section: Discussionsupporting
confidence: 49%
“…As IL-37 was identified in the diseased synovial tissue from patients with gouty arthritis, synovial cells containing both MLS and FLS were exposed to MSU in studies in vitro. Our previous study revealed that exposure of FLS to MSU crystals only transiently induced an increase in IL-1β expression, which was apparently not sufficient to initiate the inflammatory cascade as seen in resident macrophages [22]. Therefore, besides observing the inhibitory effect of rhIL-37 in vitro, we also hypothesized that MLS may play the role of resident macrophages to initiate inflammation in gouty arthritis.…”
Section: Discussionmentioning
confidence: 95%
“…Caspase1 mediated cleavage is the limiting step for processing IL-1 β into its secreted active forms [22]. Previous studies reported the activation of NLRP3/ASC/caspase1 inflammasome culminated in the production of IL-1 β [23]. ASC act as the indispensable adaptor that connects NLRP3 and procaspase1 [24].…”
Section: Discussionmentioning
confidence: 99%